Regulated deficit irrigation in persimmon trees (Diospyros kaki) cv. 'Rojo Brillante' - Buesa, Ignacio; Badal, Eduardo; Guerra, Diego; Ballester, Carlos; Bonet, Luis; Intrigliolo, Diego S. (2017)
The response of persimmon trees to deficit irrigation applied in three different phenological stages was evaluated during three consecutive seasons in a commercial orchard planted with the cv. ‘Rojo Brillante’, the most important cultivar in the Mediterranean basin. The experiment was performed in a drip-irrigated orchard located in Valencia, Spain, planted with eight-year-old trees at a spacing of 5.5 m × 4 m and grafted on the rootstock Diospyrus lotus. Three regulated deficit irrigation (RDI) regimes were tested and compared to a Control treatment irrigated at full water requirements. In the RDI treatments, moderate water restrictions (50% of Control irrigation), were applied during one of three periods (I) RDIspring, where water restrictions were applied from late May to mid July; (II) RDIsummer, deficit irrigated from mid July to late August and; (IV) RDIfall, in which water restrictions were applied from late August early September to mid November. Results showed that persimmon fruit growth was sensitive to water stress. RDI reduced final fruit weight being this reduction more marked in the most stressed treatment (RDIsummer). This decrease in fruit weight was also because spring and specially summer RDI treatments increased the number of fruit harvested. Thus, RDI techniques allowed water savings of up to 20% without any reduction in yield increasing significantly the water use efficiency. In spite of the similar yields obtained in RDI and control trees, the economic return was negatively affected by deficit irrigation, because the lower fruit weight resulted in a decrease in the fruit commercial value. In conclusion, fruit growth of persimmon cv. ‘Rojo Brillante’ was shown as highly sensitive to deficit irrigation. Based on the results obtained, RDI would need further research in order to define an RDI strategy that could increase water use efficiency without affecting the economic return.